Cause Analysis and Control Measures of Waterlogging in Shanghai Zoo Based on MIKE 21 - ZHOU Jing; WANG Huan (Renmin Zhujiang)
In order to analyze the cause of waterlogging after the drainage system of Shanghai Zoo reached the standard and explore the best control measures,data analysis and field investigation were carried out,and it was preliminarily determined that the waterlogging in the zoo was related to the poor drainage of the water system and the insufficient drainage pumping station.MIKE 21 was used to build a hydrodynamic model of the water system in the zoo,and the changes in the hydrological characteristic values of the water system under the current drainage condition were simulated and studied.It is concluded that the root cause of waterlogging in the zoo is that the drainage path is blocked,and the drainage pumping station has an insufficient scale and unreasonable layout.In order to promote drainage and remove waterlogging,the water system optimization and waterlogging facility renovation plans were proposed,and the engineering effect of each plan was simulated.Through the comparison of indicators such as drainage rate,drainage time,and maximum drainage time difference in different regions,the effect of each plan in promoting drainage and removing waterlogging was determined.In view of the engineering economy,the plan of expanding culverts and moving some culverts to the river was determined as the best,and the drainage layout was adjusted to achieve the best control effect under the specific investment.